2006
DOI: 10.4049/jimmunol.177.11.8053
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 Limits Inflammation by Localizing Mononuclear Infiltrates to the Perivascular Space during Experimental Autoimmune Encephalomyelitis

Abstract: The inflammatory response in the CNS begins with the movement of leukocytes across the blood-brain barrier in a multistep process that requires cells to pass through a perivascular space before entering the parenchyma. The molecular mechanisms that orchestrate this movement are not known. The chemokine CXCL12 is highly expressed throughout the CNS by microendothelial cells under normal conditions, suggesting it might play a role maintaining the blood-brain barrier. We tested this hypothesis in the setting of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
262
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(282 citation statements)
references
References 81 publications
(79 reference statements)
16
262
3
1
Order By: Relevance
“…Sources of CXCL12 in the normal adult CNS include neurons, endothelial cells, and meninges (13,15,25), whereas astrocyte expression of CXCL12 has been observed only in several pathological states including MS, HIV-1 encephalitis, and malignancy (29,(31)(32)(33). In studies of MS tissues, CXCL12 expression is observed within activated astrocytes in both silent and active MS lesions (34), suggesting its expression occurs in response to injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sources of CXCL12 in the normal adult CNS include neurons, endothelial cells, and meninges (13,15,25), whereas astrocyte expression of CXCL12 has been observed only in several pathological states including MS, HIV-1 encephalitis, and malignancy (29,(31)(32)(33). In studies of MS tissues, CXCL12 expression is observed within activated astrocytes in both silent and active MS lesions (34), suggesting its expression occurs in response to injury.…”
Section: Discussionmentioning
confidence: 99%
“…Frozen sections were prepared as described (25). Detection of CXCL12, GFAP, CD11b, NG2, MBP, BrDU, and CXCR4 antibodies were all assayed as described (25).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…83 Studies using AMD3100 have also been conducted in the EAE model. 84 Animals treated with this CXCR4 antagonist displayed worsened clinical disease and extensive demyelination, although numbers of mononuclear cells were similar in CNS tissues and in vehicle-treated mice. The AMD3100-treated mice, however, showed an increase in microglial activation and remarkably dispersed intraparenchymal lymphocyte infiltrates.…”
Section: Multiple Sclerosis: a Jumble Of Chemokines And Chemokine Recmentioning
confidence: 93%